2014
DOI: 10.1016/j.neurobiolaging.2014.01.135
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal neurochemical modifications in the aging mouse brain measured in vivo by 1H magnetic resonance spectroscopy

Abstract: H MRS Brain Metabolism a b s t r a c tAlterations to brain homeostasis during development are reflected in the neurochemical profile determined noninvasively by 1 H magnetic resonance spectroscopy. We determined longitudinal biochemical modifications in the cortex, hippocampus, and striatum of C57BL/6 mice aged between 3 and 24 months . The regional neurochemical profile evolution indicated that aging induces general modifications of neurotransmission processes (reduced GABA and glutamate), primary energy meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
87
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 59 publications
20
87
1
Order By: Relevance
“…In line with other longitudinal MRS studies, a significant decrease of GSH (Duarte et al, 2014) and Glu (Boumezbeur et al, 2010;Duarte et al, 2014) was observed over time in the control group. The interpretation of alterations in Glc/tCr ratio observed in this study is complicated as isoflurane anesthesia can alter glucose homeostasis Kofke et al, 1987).…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…In line with other longitudinal MRS studies, a significant decrease of GSH (Duarte et al, 2014) and Glu (Boumezbeur et al, 2010;Duarte et al, 2014) was observed over time in the control group. The interpretation of alterations in Glc/tCr ratio observed in this study is complicated as isoflurane anesthesia can alter glucose homeostasis Kofke et al, 1987).…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…Since GSH is the principal endogenous antioxidant molecule (70), it might be expected that the higher GSH levels we detected reflect lower rather than higher oxidative stress levels. However, postmortem and in vivo imaging studies in healthy humans and animals indicate that brain GSH levels are relatively stable in mature mice until late adulthood/senescence, at which point GSH may increase or decrease in different brain regions (71,9498). Thus, our observation of increased GSH levels in young adult (8–13 weeks old) Tat-expressing mice over the relatively short interval studied (8 days in MRS studies) likely indicates a pathophysiological state induced by Tat protein.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, glial oxidative metabolism was increased probably due to astrogliosis [44]. A large longitudinal MRS study in C57Bl/6 mice over 2 years further confirmed the ageinduced impairment in amino acid homeostasis, with substantial reduction in the levels of neuro-active amino acids including the major excitatory and inhibitory neurotransmitters, respectively glutamate and GABA [43]. These metabolic modifications that occur in the brain due to cellular damage accumulated during lifespan are crucial for functional deterioration in aged subjects [45] and are further accentuated in neurodegenerative disorders [42].…”
mentioning
confidence: 83%
“…In turn, defects in energy metabolism at the level of the tricarboxylic acid (TCA) cycle, electron transport chain and oxidative phosphorylation further enhance the ROS production and affects amino acid homeostasis (see [43] and references therein). Moreover, faulty mitochondrial ATP synthesis triggers higher demand from glycolysis.…”
Section: Brain Metabolism In Agingmentioning
confidence: 99%
See 1 more Smart Citation